Martial Arts and Combat Sports: Science, Research and Culture Hosted by the University of Santiago, Chile (Usach) - Herrera-Valenzuela, T (Idokan Poland Association, 2017)
Introduction. Martial arts and combat sports are practiced by thousands of persons around the world and increasingly discussed in scientific publications. Material and Methods. We describe an observational case study by describing and analyzing the activities of the "Martial Arts and Combat Sports: Science, Research and Culture" event hosted by the University of Santiago, Chile. Results. Activities were organized by the School of Physical Activity, Sports and Health, August 16-19, 2016 and included six plenary conferences, six theoretical practical workshops, one Muay Thai clinic and the launch of the Combat Sports and Martial Arts Research Group. This was the first event of this type in Chile and had 370 participants. Conclusions. In conclusion the objectives of the activities were accomplished because both science and cultural aspects of the sports were considered in an academic context. Among the participants were academics from several universities, students from physical activity-related majors, coaches, instructors and martial arts practitioners. The activities provided momentum for new challenges in 2017, including the organization of a martial arts and combat sports society and the first Chilean conference on martial arts and combat sports. © Idōkan Poland Association.